Efficacy of fluoride gel in arresting active non-cavitated caries lesions: a randomized clinical trial - Luiza Freitas Brum Souza; Bruna Venzke Fischer; Ângela DALLA Nora; Bernardo da Silva Munareto; Nathália Costa de Castro; Júlio Eduardo do Amaral Zenkner; Luana Severo Alves (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: This study evaluated the efficacy of fluoride gel in arresting active non-cavitated caries lesions in permanent teeth. This randomized, triple-blind, placebo-controlled clinical trial randomized 100 schoolchildren aged 10.7 ± 2.2 years to test treatment (1.23% acidulated phosphate fluoride [APF] gel) or control treatment (placebo gel) for 4-6 applications at weekly intervals. Data collection included the visible plaque index, gingival bleeding index, visible plaque accumulation on the occlusal surfaces, eruption stage, and dental caries. The association between group and lesion arrestment was assessed using logistic regression, and estimates were adjusted for plaque accumulation over the lesion at baseline, surface type, and tooth type. Models were fitted using generalized estimating equations for accounting for the clustering of data (i.e., the same individual contributed > 1 lesion). Ninety-eight children completed the study (48 fluoride and 50 placebo). When all dental surfaces were analyzed, the likelihood of lesion arrestment was similar between both groups (p > 0.05). A secondary analysis including only the occlusal lesions in molars showed that for teeth under eruption, lesions receiving the 1.23% APF gel were about 3-fold more likely to become arrested than lesions receiving the placebo gel (OR = 2.85; 95%CI = 1.23-6.61; p = 0.01). No significant difference was detected for molars with complete eruption (p > 0.05). The benefit of fluoride gel for arresting non-cavitated caries lesions could not be identified by clinical assessment in this short-term trial. Notwithstanding, when the cariogenic challenge was greater (as on the occlusal surfaces of erupting molars), 1.23% APF gel treatment was an important tool for caries control.